Про варiацiйний принцип Гамiльтона–Остроградського i початково-крайовi динамiчнi задачi електропружностi - Шульга, М.О. (Видавничий дім "Академперіодика" НАН України, 2008)
The Hamilton–Ostrogradskii variation principle is formulated, and, on its basis, the definition of initial-boundary dynamic problems of electroelasticity is grounded.